Pengembangan Buku Ajar Konsep Dasar IPA Biologi Berbasis Science Process Untuk Meningkatkan Keterampilan Proses Sains dan Hasil Belajar Kognitif Mahasiswa PGMI - Resty Rahmatika (STAI AL-AMIN, 2026)
This study aims to produce a valid, practical, and effective Science Process-based Biology Fundamentals textbook to improve PGMI students' science process skills and cognitive learning outcomes. This study uses Plomp's development research through three stages of activities. The subjects in this study were selected using purposive sampling with a sample of 28 students who took the MI Science Material course in the 2024-2025 academic year. The data collection technique used instruments in the form of science process skills and cognitive learning outcome test sheets, questionnaires, and validation sheets. The data analysis technique examined the improvement in students' science process skills and cognitive learning outcomes based on pretest and posttest scores tested through the N-Gain classical score. The results showed that the developed teaching materials were valid with an average textbook validity of 3.85. In science process skills, the average pretest score was 29.29 and the posttest score was 78.25 with an increase of 69%, and in cognitive learning outcomes, the average pretest score was 49.58 and the posttest score was 75.00 with an increase of 50%, which is considered effective. The overall student response questionnaire results were 94.71% in the very strong category, meaning that the textbook is practical to use. Thus, it can be concluded that the MI Biology Science Process-based Basic Science Concepts textbook is valid, practical, and effective.